Amiodarone-induced type 2 thyrotoxicosis. Issue 1 (8th January 2021) - Portelli, Darryl; Mifsud, Simon; Abela, Alexia; Fava, Stephen
Abstract : The authors present a case of a 55-year-old gentleman with a medical history of atrial fibrillation on amiodarone who presented with weight loss, palpitations and exertional dyspnoea. Thyroid function tests revealed thyrotoxicosis with a free thyroxine (T4) of 117 pmol/L and a thyroid-stimulating hormone (TSH) of <0.008 mIU/L. Interleukin-6 level was low. The negative TSH-receptor antibody status, the presence of a small thyroid gland with heterogeneous echotexture and decreased internal vascularity on ultrasound together with the relatively quick drop in free T4 and free tri-iodothyronine (T3) levels once prednisolone therapy was added to carbimazole suggested that this was typical of amiodarone-induced thyrotoxicosis (AIT) type 2. Subsequently, carbimazole was discontinued and treatment with prednisolone was continued. This case highlights that AIT management may be challenging and it is of paramount importance to establish the type of AIT present as this will guide management and is key to improving prognosis.